Improvement of the O2 storage/release rate of YMnO3 nanoparticles synthesized by the polymerized complex method. Issue 4 (2nd January 2020) - Asakura, Yusuke; Miyake, Amiko; Otomo, Mayu; Yin, Shu
Abstract : YMnO3 nanoparticles synthesized by the polymerized complex method exhibited a high O2 storage/release rate because of high O2 diffusion induced by their small size. Abstract : YMnO3 nanoparticles with a diameter of ca. 100 nm, which were synthesized by the polymerized complex method, exhibited a high O2 storage/release rate, because nanoparticle morphology increased the O2 accessible surface area of the material. This material with a high O2 storage/release rate is promising as a separator of O2 from air.